(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
The metropolitan area of Buenos Aires, owns 36% of the population and represents over 60% of industrial GDP Argentina, in just under 4% of the territory of the Province of Buenos Aires. In this context, the county of La Matanza, the most populous county and the largest contribution to provincial industrial GDP (22%), is characterized by having a very diverse set of industries, mainly SMEs; however sprawl of industrial activities in number and variety, also multiplied the creation of formal and informal institutions without rational location criteria, which are now a serious problem for industrial urban planning. This paper attempts to define a model that defines the main variables that determine industrial location in the district, serving as input for future policy and industrial relocation filing for the district.